'We had to change to single beds because I itch in the night': a qualitative study of the experiences, attitudes and approaches to coping of patients with cutaneous T‐cell lymphoma. (1st July 2015) - Beynon, T.; Selman, L.; Radcliffe, E.; Whittaker, S.; Child, F.; Orlowska, D.; Morgans, C.; Morris, S.; Harding, R.
Summary: Background: Primary cutaneous T‐cell lymphoma (CTCL) is a rare but prevalent condition which can have a significant impact on many aspects of quality of life. However, there is little evidence of patients' lived experience of CTCL. Objectives: To understand in greater depth patients' experiences of living and coping with CTCL, and to inform the development of models of care for this population in line with U.K. guidelines. Methods: Semi‐structured interviews were conducted with a purposive sample of patients with CTCL who attended an inner‐city teaching hospital. Participants were purposively selected according to their disease stage, age, sex and ethnicity. Results: Nineteen patients with CTCL (stages IB–IVB), aged between 41 and 83 years, participated in a single interview. This included 10 men; 15 people identified themselves as white British. Interviews lasted a median of 55 (range 28–170) min. Two main themes emerged: issues regarding diagnosis, particularly a perceived delay in diagnosis, and the impact of CTCL (subthemes related to physical well‐being, practical concerns and psychological and social well‐being and coping). Conclusions: Findings from this study illuminate the diverse effects of CTCL on patients' lives. The universal experience of delays in diagnosis was striking and a concern to patients. The disease, particularly its physical symptoms, had a significant impact on patients' lives, including employment, leisure and relationships. Despite the symptom burden and its impact, participants described effective coping strategies such as drawing on social support, maintaining normal lives and becoming well informed about CTCL. Proactive holistic assessment and management of the range of patient concerns is needed in providing care for patients with CTCL and their family and friends.